Hsp90 and cochaperones have two genetically distinct roles in regulating eEF2 function. - Melody D Fulton; Danielle J Yama; Ella Dahl; Jill L Johnson (PLoS Genetics)
Protein homeostasis relies on the accurate translation and folding of newly synthesized proteins. Eukaryotic elongation factor 2 (eEF2) promotes GTP-dependent translocation of the ribosome during translation. eEF2 folding was recently shown to be dependent on Hsp90 as well as the cochaperones Hgh1, Cns1, and Cpr7. We examined the requirement for Hsp90 and cochaperones more closely and found that Hsp90 and cochaperones have two distinct roles in regulating eEF2 function. Yeast expressing one group of Hsp90 mutations or one group of cochaperone mutations had reduced steady-state levels of eEF2. The growth of Hsp90 mutants that affected eEF2 accumulation was also negatively affected by deletion of the gene encoding Hgh1. Further, mutations in yeast eEF2 that mimic disease-associated mutations in human eEF2 were negatively impacted by loss of Hgh1 and growth of one mutant was partially rescued by overexpression of Hgh1. In contrast, yeast expressing different groups of Hsp90 mutations or a different cochaperone mutation had altered sensitivity to diphtheria toxin, which is dictated by a unique posttranslational modification on eEF2. Our results provide further evidence that Hsp90 contributes to proteostasis not just by assisting protein folding, but also by enabling accurate translation of newly synthesized proteins. In addition, these results provide further evidence that yeast Hsp90 mutants have distinct in vivo effects that correlate with defects in subsets of cochaperones.